2022
DOI: 10.1007/s00213-022-06195-5
|View full text |Cite
|
Sign up to set email alerts
|

Genetics and epigenetics: paternal adolescent ethanol consumption in serotonin transporter knock-out rats and offspring sensitivity to ethanol

Abstract: Rationale Alcohol use disorder (AUD) is shown to have an overall heritability of around 50%. One of the genes associated with AUD is SLC6A4 (solute carrier family 6 member A4) which codes for the serotonin transporter (SERT). The study looked at serotonin dysfunction on ethanol consumption in adolescents and the subsequent intergenerational effects of drinking by using a rat model: SERT+/+ (regular functioning), SERT+/− (50% transporter reduction) and SERT−/− (complete reduction). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
16
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(25 citation statements)
references
References 71 publications
9
16
0
Order By: Relevance
“…While anxiety and hyperactivity are not mutually exclusive, we chose to refrain from forming a specific hypothesis related to housing on the SAT, and leave this largely exploratory. We did expect to see greater exploration, and less anxiety in the female animals compared to the males, as previous research has shown that female rats tend to be more active (Healy et al, 2022;Hussain et al, 2022;Nelson et al, 2019;).…”
Section: Animal Modelsmentioning
confidence: 90%
See 4 more Smart Citations
“…While anxiety and hyperactivity are not mutually exclusive, we chose to refrain from forming a specific hypothesis related to housing on the SAT, and leave this largely exploratory. We did expect to see greater exploration, and less anxiety in the female animals compared to the males, as previous research has shown that female rats tend to be more active (Healy et al, 2022;Hussain et al, 2022;Nelson et al, 2019;).…”
Section: Animal Modelsmentioning
confidence: 90%
“…We also expected that the female rats would consume more ethanol overall (and show a higher preference) than the male rats during the IATBCP, owing to the previous findings of the literature above (Hussain et al, 2022;Moore & Lynch, 2015).…”
Section: Animal Modelsmentioning
confidence: 97%
See 3 more Smart Citations